Does geodemographic segmentation explain differences in route of cancer diagnosis above and beyond person-level sociodemographic variables?. (12th August 2020) - Bright, C J; Gildea, C; Lai, J; Elliss-Brookes, L; Lyratzopoulos, G
ABSTRACT: Background: Emergency diagnosis of cancer is associated with poorer short-term survival and may reflect delayed help-seeking. Optimal targeting of interventions to raise awareness of cancer symptoms is therefore needed. Methods: We examined the risk of emergency presentation of lung and colorectal cancer (diagnosed in 2016 in England). By cancer site, we used logistic regression (outcome emergency/non-emergency presentation) adjusting for patient-level variables (age, sex, deprivation and ethnicity) with/without adjustment for geodemographic segmentation (Mosaic) group. Results: Analysis included 36 194 and 32 984 patients with lung and colorectal cancer. Greater levels of deprivation were strongly associated with greater odds of emergency presentation, even after adjustment for Mosaic group, which nonetheless attenuated associations (odds ratio [OR] most/least deprived group = 1.67 adjusted [model excluding Mosaic], 1.28 adjusted [model including Mosaic], P < 0.001 for both, for colorectal; respective OR values of 1.42 and 1.18 for lung, P < 0.001 for both). Similar findings were observed for increasing age. There was large variation in risk of emergency presentation between Mosaic groups (crude OR for highest/lowest risk group = 2.30, adjusted OR = 1.89, for colorectal; respective values of 1.59 and1.66 for lung). Conclusion: Variation in risk of emergency presentation in cancer patients can be explained by geodemography, additional to deprivation group and age. The findings support proof of concept for public health interventions targeting all the examined attributes, including geodemography.